Разработка метода корректной дозировки озона в процедурах внутривенной инфузии озонированного физиологического раствора - Кипенский, Андрей Владимирович; Глухенькая, Т. А. (НТУ "ХПИ", 2014)
Одним из немедикаментозных методов лечения является озонотерапия, которая достаточно часто проводится в виде внутривенных инфузий озонированного физиологического раствора. В работе показано: концентрация озона в таком растворе существенно зависит от ряда факторов, что, в свою очередь, влияет на дозу озона, получаемую пациентом во время процедуры инфузии. Получены расчетные выражения и предложен метод корректной дозировки озона при проведении внутривенных инфузий. Использование предложенного метода в медицинской практике позволит достаточно точно обеспечивать дозу озона, получаемую пациентом в процессе проведения процедуры.

One of the non-drug treatments is ozone therapy, which is often enough conducted in the form of intravenous infusions of ozona ted soline solution. The paper shows: the concentration of ozone in this solution depends essentially on a number of factors, which in turn affects the ozone dose received by the patient during an infusion procedure. The calculated expression are obtained and proposed a method of correct dosage of ozone during intravenous infusion. The experimental results showed that the rate of ozone saturation of saline solutions is not the same for different manufacturers. Saturation velocity saline ozone and its rate of decomposition substantially depend on the ambient temperature and, respectively - temperature of the solution. Stabilization of the concentration of ozone in ozonized saline was made possible due to the subsequent solution bubbling ozone-oxygen mixture with a strictly predetermined concentration of ozone during the procedure of infusion. Using the proposed method is correct dosage of ozone in me-practice their medi-allow sufficiently accurate to provide ozone dose received by the patient during the proce dure intravenous infusion of ozonated saline.
Development metod correct dasage of ozone in procedure intravenous infusion ozonized soline solution
Keywords: доза озона; метод дозировки; ozone therapy; intravenous infusion; soline solution; ozone dose; method of dosage